This preview shows page 1. Sign up to view the full content.
Unformatted text preview: t A).
Proof.
E is obtained from In by interchanging two rows: Then
det E = −1 and so det(EA) = − det A = (det E )(det A).
E is obtained from In by multiplying a row by λ = 0: Then
det E = λ and therefore det(EA) = λ det A = (det E )(det A).
E is obtained from In by adding λ times one row to another
row: Then det E = 1 and so
det(EA) = det A = (det E )(det A). Outline Linearity of the Determinant Determinants and Invertibility Determinants and Products The Determinant of a Product of Matrices Theorem
If A and B are n × n matrices, then
det(AB ) = (det A)(det B ). Determinants and Inverses Outline Linearity of the Determinant Determinants and Invertibility Determinants and Products Determinants and Inverses Proo...
View
Full
Document
This note was uploaded on 02/10/2014 for the course MATH 2270 taught by Professor Kenyonj.platt during the Spring '14 term at Snow College.
 Spring '14
 KenyonJ.Platt
 Linear Algebra, Algebra, Determinant

Click to edit the document details